Thin Layer Adsorbent For The Removal Of Methylene Blue Via Brushing, Airbrushing And Electrospinning - Jalil, Aiizat Ikhwan Abdul (2019)
PaintosorpTM is an innovative adsorbent coating that was designed for the removal of dyes from industrial wastewater. This research focuses on the methods of applying PaintosorpTM and PVB/Bentonite via various methods such as brushing, airbrushing and electrospinning. Airbrushing uses air pressure to paint PaintosorpTM in miniscule droplets meanwhile electrospinning utilizes high voltage to weave the adsorbent into nanofibers. The adsorption ability of airbrushed PaintosorpTM and electrospun PVB/Bentonite nanofiber was tested with the change in stirring velocity, pH and initial adsorbate concentrations. PaintosorpTM recorded high adsorption of 100% removal for both low (20 ppm) and high concentrations (200 ppm) in the first 4 hours of the experiment and is affected slightly with the change pH and stirring velocity. The adsorption capacity of airbrushed PaintosorpTM were at 45.0 mg/g when tested with high concentration of MB of 200 ppm. The electrospun PVB/Bentonite nanofiber had lower removal compared to PaintosorpTM where it had only 88% removal of MB at 20 ppm and 33% removal at 200 ppm. The adsorption capacity of the electrospun nanofiber were at 47.7 mg/g when tested with 200 ppm. The changes in pH and initial adsorbate concentrations had significant effect on its MB removal. The PVB/Bentonite nanofiber performs poorly in acidic conditions and the MB removal drops as the concentration increase from 100 ppm to 200 ppm, where the MB removal was at 47% removal to 33% removal respectively. The stirring rate only had slight effect on the nanofiber adsorption ability. The characterization of the airbrushed PaintosorpTM coating and PVB/Bentonite nanofibers were done using SEM, EDX and FTIR. It is found that the nanofiber were more porous than the coating but the coating had higher presence of Al and Si atoms. The airbrushed PaintosorpTM coating fits the Freundlich isotherm model meanwhile the PVB/Bentonite nanofiber fits the Langmuir model. The adsorbent kinetics studies revealed that both the adsorbent coating and nanofiber fits the pseudo-second-order model.